Yield and physicochemical characterization of coriander essential oil extracted by steam entrainment in a modular equipment (Technological Innovations Journal, 2022)
This work presents a study of the physicochemical characterization, compounds of the essential oil of coriander (coriandrum sativum) and the yield extracted by steam dragging. For this purpose, gas chromatography was chosen, the determination of the variables that influence the extraction and the evaluation of the yield of coriander essential oil. The extraction process was carried out by steam dragging, where the following parameters were analyzed: amount of raw material, water flow and time. In order to obtain the best yield of essential oil extraction. For the results, the 23 factorial design was used without repetitions, thus obtaining the best result, giving us the optimal yield 0.07625% (1.1 ml) of 4.0 kg of the coriander sample under the following conditions: Water flow 150 L/h and at a time of 120 minutes, according to the physicochemical characterization, density 0.9400 g/mL, refractive index 1.513, acidity index 4.29% and peroxide index 0.84 meq/kg, likewise, it was found to contain Aromatic compounds: Nonyl acetate (15.70%), n-decanal (15.13%), trans-2-octenal (13.23%), lauric aldehyde (5.08%), linalool (1.58%) , trans-2-nonenal (1.12%), geraniol (0.08%). It is concluded that time influences the extraction of the raw material. In the case of the quantity and flow of water, there is an influence on the extraction of oil, however, these are not significant, verifying that it does contain aromatic chemical compounds.
Keywords: coriandum satuvim; essential oil; steam entrainment; gas chromatography